Sosialisasi dan Pelatihan Pembuatan Eco Craft untuk Meningkatkan Ekonomi Kreatif pada Ibu PKK Desa Bancong - Fitria Lusiyanti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
This community service program was conducted to empower members of the PKK women’s group in Bancong Village, Wonoasri District, Madiun Regency through training in the production of eco crafts using household plastic waste. The background of this activity stems from the community’s low awareness of waste management and limited access to creative economic opportunities in the village. The aim of the training was to improve participants’ knowledge, technical skills, and motivation in recycling plastic waste into useful and marketable products. The implementation method consisted of initial coordination, hands-on training workshops, and post-training evaluation. Evaluation was carried out using questionnaires and documentation of the resulting products. The results showed significant improvement in five key areas: knowledge, engagement, practical skills, motivation, and participants’ perceptions of the importance of waste management and entrepreneurship. Before the training, most participants lacked basic skills in waste processing, but after the sessions, they were able to produce items such as bags, tissue holders, and coasters with potential market value. The training not only enhanced individual skills but also fostered environmental awareness and inspired participants to initiate home-based businesses using eco-friendly materials. This program has shown positive implications for strengthening the local creative economy and can be replicated in similar communities to support community-based waste management efforts. Keywords: community empowerment, creative economy, eco craft, plastic waste, training